2021
DOI: 10.3389/fcimb.2021.723821
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Periodontal Bacteria of Edo and Modern Periods Using Novel Diagnostic Approach for Periodontitis With Micro-CT

Abstract: Ancient dental calculus, formed from dental plaque, is a rich source of ancient DNA and can provide information regarding the food and oral microbiology at that time. Genomic analysis of dental calculus from Neanderthals has revealed the difference in bacterial composition of oral microbiome between Neanderthals and modern humans. There are few reports investigating whether the pathogenic bacteria of periodontitis, a polymicrobial disease induced in response to the accumulation of dental plaque, were different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Human skeletons from the 18 th and 19 th centuries show high abundance of F. nucleatum subsp. vincentii with P. gingivalis and Prevotella pleuritidis , and this is maintained in modern samples [ 58 ]. F. nucleatum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Human skeletons from the 18 th and 19 th centuries show high abundance of F. nucleatum subsp. vincentii with P. gingivalis and Prevotella pleuritidis , and this is maintained in modern samples [ 58 ]. F. nucleatum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the non-mineralized bio lm gets mineralized to form dental calculus, which contains enormous amounts of oral bacteria and their DNA [40]. It could then be suggested that mineralized dental calculus could reference the genome information of the bacterial compositions in non-mineralized dental plaque, even ancient samples [41].…”
Section: Discussionmentioning
confidence: 99%
“…Taxon pairs with SparCC values ≥0.9 are considered as having a co-occurrence relationship with a positive correlation. The parameters for this analysis other than the SparCC value were as previously described (Shiba et al, 2016(Shiba et al, , 2021Komatsu et al, 2020;Nemoto et al, 2021). The networks were visualized using the Cytoscape software v.2.8.…”
Section: Discussionmentioning
confidence: 99%